(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 12-year-old immunized boy, 3rd issue of consanguineous parents, presented with jaundice for the last 4 months and gradual abdominal distension for last 2 months. Mother also mentioned the swelling of both ankles for the same duration. He had anorexia, nausea and generalized weakness. There was no history of previous jaundice, blood transfusion, surgical procedure, history of taking offending drugs, no family history of liver disease, deterioration of school performance or neuropsychiatric manifestations, bleeding manifestations, behavioral abnormality, altered consciousness or convulsion.